Integrating qualitative and quantitative methods : a pragmatic approach - Morgan, David L. (Sociologist) (Thousand Oaks, California : SAGE Publications, Inc., 2014)
'This is a book about research design. In particular, it is about research designs for projects that collect both qualitative and quantitative data, so that their combined strengths will accomplish more than would have been possible with any one method. The approach presented here is broadly interdisciplinary, because Mixed Methods Research has interested social scientists from a great many fields, including: Anthropology, Communication, Criminal Justice, Education, Evaluation, Nursing, Organizational Behavior, Psychology, Political Science, Public Administration, Public Health, Sociology, Social Work, and Urban Studies. Because this book emphasizes practical research designs, it will be most useful to practicing researchers -- including both students who intend to pursue such a career and those who already devote their energy to collecting and analyzing data. Whether you are a student or a more experienced researcher, you will learn how Mixed Methods Research gets done in the real world.'--Publisher's website.
Part 1: The Logic of Mixed Methods Research. An Introduction and Overview ; Pragmatism as a Paradigm for Mixed Methods Research ; Research Design and Research Methods ; Motivations for Using Mixed Methods Research ; The Sequential Priorities Model -- Part 2: Four Basic Designs. Preliminary Qualitative Inputs to Core Quantitative Research Projects ; Preliminary Quantitative inputs to Core Qualitative Research Projects ; Follow-up Qualitative Extensions to Core Quantitative Research Projects ; Follow-up Quantitative Extensions to Core Qualitative Research Projects -- Part 3: Additional issues. Multipart Sequential Designs ; Finding the Expertise to Combine Multiple Methods ; Conclusions: Further Thoughts About Research Design.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Statistical methods; Qualitative research; Qualitative research; Social sciences -- Research -- Methodology; Social sciences -- Statistical methods; Empirische Sozialforschung; Forschungsmethode; Quantitative Methode; Qualitative Methode; Sociaalwetenschappelijk onderzoek; Onderzoeksmethoden; Leermiddelen (vorm)